Pengaruh Perendaman Basis Gigi Tiruan Resin Akrilik Polimerisasi Panas dalam Larutan Sodium Hipoklorit dan Vinegar Cuka Putih Terhadap Kekasaran Permukaan dan Stabilitas Warna - M Zulkarnain; Jefferson Daniel B (Jurnal Material Kedokteran Gigi, 2014)
Heat-polymerized acrylic resin is a material that oftenly used to manufacture denture base. As the use of denture base material, it will be contaminated by microorganisms that requiring cleansing. One of method that is commonly used for cleaning denture is chemical method by immersing denture base into disinfectant. Sodium hypochlorite and white vinegar are ingredients that can be used as denture cleansers, but according to studies those ingredients can affect the physical properties of denture such as surface roughness and color stability. This study aims to determine the effect of heatpolymerized acrylic resin denture base immersion using sodium hypochlorite and white vinegar on surface roughness and color stability. This study was carried out on cylindrical heat-polymerized acrylic resin samples with a height of 0,5 mm and a diameter of 50 mm to test surface roughness and color stability. The design of this study is experimental laboratory. 27 samples of heat-polymerized acrylic resin are used to measure surface roughness and color stability. The data were analyzed by one way ANOVA test and LSD (Least Significance Difference) test. The results of the study shows that there was effect of heat-polymerized acrylic resin denture base immersion using sodium hypochlorite 0,5% and white vinegar 5% for 1,5 years on surface roughness and color stability.